TINGKAT KEPUASAN PEMUSTAKA TERHADAP APLIKASI IPUSNAS MENGGUNAKAN MODEL DeLone and McLean - Amelia Putri, Siska; Desriyeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the level of student satisfaction of the Library and Information Science Study Program at Padang State University with the iPusnas application as librarians based on the dimensions of system quality, information quality, service quality, actual use or intention to use, user satisfaction, and net benefits according to the DeLone and McLean model. This study used a quantitative descriptive method with 78 students of the Library and Information Science Study Program at Padang State University from the classes of 2021, 2022, 2023, and 2024 who used the iPusnas application as subjects. The results showed that the level of student satisfaction of the Library and Information Science Study Program at Padang State University with the iPusnas application was in the high category with an average score of 81.77. This indicates that the iPusnas application has successfully met the information needs of students as academic librarians, although there are still several aspects that need to be improved. This study recommends technical improvements to the system, the addition of copies of popular books, and regular collection updates to continuously increase user satisfaction.